Greetings in male Guinea baboons and the function of rituals in complex social groups. Issue 125 (December 2018) - Dal Pesco, Federica; Fischer, Julia
Abstract: Ritualized greetings, defined as exchanges of non-aggressive signals, are common among males living in multi-male groups and are thought to balance the trade-offs of male co-residence. While ritualized greetings are widespread in the animal kingdom, the behavioral repertoire described in the genus Papio is exceptional, as it involves potentially harmful behaviors such as genital fondling. Although greetings are one of the most striking male social interactions in baboons, their function is still disputed. We investigated the function of male–male ritualized greeting behavior in wild Guinea baboons. This species lives in multilevel societies where several 'units' comprising a primary male, females with young, and occasionally a secondary male form a 'party', and two to three parties form a gang. Adult males maintain affiliative relationships with preferred male partners whom they support in coalitions, regardless of kinship. We examined the social behavior of 24 adolescent and adult males (∼900 h focal observations) in the Niokolo-Koba National Park, Senegal, to test whether greetings reflect relationship quality or function to buffer tension. Greetings were ten times more frequent than aggression and twice as frequent as affiliation. Neither dyadic aggression nor tense context predicted greeting rate, discounting the buffering hypothesis. Greetings occurred almost exclusively between males of the same party, even when other parties were around. Within parties, spatially tolerant partners greeted more frequently but dyads did not greet due to proximity prior to the greeting. Although affiliation did not predict overall greeting rate, intense and potentially costly greetings were more likely between males with stronger affiliative relationships. Greetings in Guinea baboons appear to signal commitment among party members, test relationships among spatially tolerant partners, and accentuate relationship strength among highly affiliated males. Although ritualized baboon greetings lack the symbolic component of human rituals, they appear to serve similar functions, specifically to strengthen in-group affiliation and promote cooperation.